Bloom Syndrome Helicase Compresses Single‐Stranded DNA into Phase‐Separated Condensates. Issue 39 (23rd August 2022) - Wang, Teng; Hu, Jiaojiao; Li, Yanan; Bi, Lulu; Guo, Lijuan; Jia, Xinshuo; Zhang, Xia; Li, Dan; Hou, Xi‐Miao; Modesti, Mauro; Xi, Xu‐Guang; Liu, Cong; et al.
Abstract: Bloom syndrome protein (BLM) is a conserved RecQ family helicase involved in the maintenance of genome stability. BLM has been widely recognized as a genome "caretaker" that processes structured DNA. In contrast, our knowledge of how BLM behaves on single‐stranded (ss) DNA is still limited. Here, we demonstrate that BLM possesses the intrinsic ability for phase separation and can co‐phase separate with ssDNA to form dynamically arrested protein/ssDNA co‐condensates. The introduction of ATP potentiates the capability of BLM to condense on ssDNA, which further promotes the compression of ssDNA against a resistive force of up to 60 piconewtons. Moreover, BLM is also capable of condensing replication protein A (RPA)‐ or RAD51‐coated ssDNA, before which it generates naked ssDNA by dismantling these ssDNA‐binding proteins. Overall, our findings identify an unexpected characteristic of a DNA helicase and provide a new angle of protein/ssDNA co‐condensation for understanding the genomic instability caused by BLM overexpression under diseased conditions. Abstract : Single‐molecule optical‐tweezers analysis revealed that Bloom syndrome helicase can undergo phase separation and form condensates on single‐stranded (ss) DNA, giving rise to the compression and condensation of ssDNA into the condensates that are stable in the presence of a high resistant force.